2018
DOI: 10.18178/ijmmm.2018.6.4.394
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Tin addition on the Microstructure, Melt Properties and Mechanical Properties of Ag-Cu-Zn-Sn Braze Filler

Abstract: The influence of Sn addition on the microstructure, melt properties and mechanical properties of Ag-Cu-Zn-Sn braze filler were investigated in this study. Microstructural analysis reveal that increase of Sn content with increased the eutectic phase and promote the formation of Cu 3 Sn intermetallic compound.The differential thermal analysis show that increase of Sn content dramatically decrease the melting temperature of the Ag-40Cu-1Zn-7Sn braze filler are 700 o C. The tensile strength and elongation of braz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
(11 reference statements)
0
1
0
Order By: Relevance
“…The decrease of Ag content will seriously affect the brazing performance of silverbased filler metals [8,9]. Thus far, many attempts have been made to solve the problem and to produce cadmium-free low-silver alloys that have similar characteristics of low melting point, excellent fluidity and high joint strength, several novel brazing filler metals have been developed, such as AgCuTi [10], AgCuZnMnNi [11], AgCuZnSn [12,13], AgCuZnSnIn [14], AgCuZnSnCe [15] and AgCuZnSnGa [16], which have resulted in the initial application and development of Cd-free silver-based filler metals in green manufacturing. Lai [17] has reported that the addition of Ga, Sn, In, and Ni can optimize the microstructure and mechanical properties of 30AgCuZn filler metal, but the Ag content is still very high.…”
Section: Introductionmentioning
confidence: 99%
“…The decrease of Ag content will seriously affect the brazing performance of silverbased filler metals [8,9]. Thus far, many attempts have been made to solve the problem and to produce cadmium-free low-silver alloys that have similar characteristics of low melting point, excellent fluidity and high joint strength, several novel brazing filler metals have been developed, such as AgCuTi [10], AgCuZnMnNi [11], AgCuZnSn [12,13], AgCuZnSnIn [14], AgCuZnSnCe [15] and AgCuZnSnGa [16], which have resulted in the initial application and development of Cd-free silver-based filler metals in green manufacturing. Lai [17] has reported that the addition of Ga, Sn, In, and Ni can optimize the microstructure and mechanical properties of 30AgCuZn filler metal, but the Ag content is still very high.…”
Section: Introductionmentioning
confidence: 99%